2019
DOI: 10.1016/j.jinteco.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The interconnections between services and goods trade at the firm-level

Abstract: In this paper we study how international trade in goods and services interact at the firm level. Using a rich dataset on Belgian firms during the period 1995-2005, we show that: i) firms are much more likely to source services and goods inputs from the same origin country rather than from different ones; ii) increases in barriers to imports of goods reduce firm-level imports of services from the same market, and conversely. We build upon a discrete-choice model of goods and services input sourcing that can rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 42 publications
2
51
0
2
Order By: Relevance
“…Column 1 of Table 6 reports Finally, the joint effect of all five policy induced services trade barriers are reported in Column 7 and only for Transport and W&R are negative and significant. These results are in line with Nordås and Rouzet (2015) and Ariu et al (2016) who found similar results by using OECD STRI index and OECD PMR index, respectively.…”
Section: Baseline Resultssupporting
confidence: 91%
“…Column 1 of Table 6 reports Finally, the joint effect of all five policy induced services trade barriers are reported in Column 7 and only for Transport and W&R are negative and significant. These results are in line with Nordås and Rouzet (2015) and Ariu et al (2016) who found similar results by using OECD STRI index and OECD PMR index, respectively.…”
Section: Baseline Resultssupporting
confidence: 91%
“…They found a statistically significant and negative effect on total services and business services imports, but also report statistically insignificant results at the sector level. Another approach to identify country‐specific trade restrictions is to add intra‐national trade to the data and interacting country‐specific trade barriers with an international trade dummy (Benz, 2017; Benz & Jaax, 2020) or an FTA dummy (Ariu et al., 2017).…”
Section: Services Trade Policy and Performancementioning
confidence: 99%
“…Other recent research highlights the close relationship between goods and services trade, finding that companies are more likely to source services and goods inputs from the same country, and that increases in barriers to goods imports reduce services imports from the same market, and vice-versa (Ariu et al, 2019).…”
Section: Restrictions On Services Trade Negatively Impact Manufacturimentioning
confidence: 99%